2010
DOI: 10.1016/j.oraloncology.2010.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Downstream targets of FOXM1: CEP55 and HELLS are cancer progression markers of head and neck squamous cell carcinoma

Abstract: AbbreviationsHNSCC, head and neck squamous cell carcinoma; FOXM1, forkhead box M1; CEP55, centrosomal protein 55; HELLS, lymphoid specific helicase; qPCR, absolute real time reverse transcription quantitative polymerase chain reaction; NHOK, primary normal human oral keratinocytes; LnMet, lymph node metastasis; FFPE, formalin-fixed paraffin embedded. ABSTRACTWe recently showed that upregulation of a key oncogene FOXM1 precedes head and neck squamous cell carcinoma (HNSCC) malignancy. Furthermore, we also iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 44 publications
5
68
0
Order By: Relevance
“…Reports show that LSH contributes to the malignant progression of prostate cancer, melanoma, head and neck cancer, etc. (12,40,41); however, the molecular mechanisms are not well understood. Here, we demonstrated that LSH was linked to cancer progression of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…Reports show that LSH contributes to the malignant progression of prostate cancer, melanoma, head and neck cancer, etc. (12,40,41); however, the molecular mechanisms are not well understood. Here, we demonstrated that LSH was linked to cancer progression of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…The uncontrolled G2 to M cell cycle progression is essential for oral cancer progression, and is characterised by an increase in the tumour size 43 . The transcription factors associated with this pathway, PLK1 and FOXM1, activate CEP55, a cytokinesis promoter identified as a key marker of tumor formation and progression 44 . Earlier CEP55…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although these genes may be upregulated simply due to increased proliferative capacity of carcinomas, aurora kinase A has been previously investigated in UCa, where it is commonly found to be amplified [13] and may be a potential novel therapeutic target [14], which validates our results. A second category of upregulated genes included nicotine-responsive genes, as identified in both lung and head and neck squamous cancers, and include TTK , CEP55 , PRC1 and FOXM1 [15-18]. As tobacco smoking is a preeminent risk factor for the development of both UCa and SCCa of the bladder, these genes may reflect this association.…”
Section: Resultsmentioning
confidence: 99%